Quality assurance of the solar UV network in the Antarctic - Lakkala, Kaisa; Redondas, Alberto; Meinander, Outi; Torres, Carlos; Koskela, Tapani; Cuevas, Emilio; Taalas, Petteri; Dahlback, Arne; Deferrari, Guillermo Alejandro; Edvardsen, Kåre; Ochoa, Héctor (Journal of Geophysical Research: Atmospheres, 2005)
Measuring ultraviolet radiation in the Antarctic region, where weather conditions are extremely challenging, is a demanding task. Proper quality control of the measurements and quality assurance of the data, which are the basis of all scientific use of data, has to be especially well planned and executed. In this paper we show the importance of proper quality assurance and describe the methods used to successfully operate the NILU-UV multichannel radiometers of the Antarctic network stations at Ushuaia, 54°S, and Marambio, 64°S. According to our experience, even though multichannel instruments are supposed to be rather stable as a function of time, severe drifts can occur in the sensitivity of the channels under these harsh conditions. During 2000–2003 the biggest drifts were 35%, both at Ushuaia and Marambio, with the sensitivity of the channels dropping at different rates. Without proper corrections in the data, this would have seriously affected the calculated UV dose rates. As part of the quality assurance of the network a traveling reference NILU-UV, which was found to be stable, was used to transfer the desired irradiance scale to the site NILU-UV data. Relative lamp tests were used to monitor the stability of the instruments. Each site NILU-UV was scaled channel by channel to the traveling reference by performing solar comparisons. The method of scaling each channel separately was found to be successful, even though the differences between the raw data of the site NILU-UV and the reference instruments were, before the data correction, as much as 40%. After the correction, the mean ratios of erythemally weighted UV dose rates measured during the solar comparisons in 2000–2003 between the reference NILU-UV and the site NILU-UV were 1.007 ± 0.011 and 1.012 ± 0.012 for Ushuaia and Marambio, respectively, when the solar zenith angle varied up to 80°. These results make possible the scientific use of NILU-UV data measured simultaneously at quite different locations, e.g., the Antarctic and Arctic, and the method presented is also practicable for other multichannel radiometer networks.
Keywords: Antarktis; UV-stråling; meteorologi; målinger; ultrafiolett stråling

Validation of the TROPOspheric Monitoring Instrument (TROPOMI) surface UV radiation product - Lakkala, Kaisa; Kujanpää, Jukka; Brogniez, Colette; Henriot, Nicolas; Arola, Antti; Aun, Margit; Auriol, Frédérique; Bais, Alkiviadis F; Bernhard, Germar; De Bock, Veerle; Catalfamo, Maxime; Deroo, Christine; et al. (Atmos. Meas. Tech., 2020)
The TROPOspheric Monitoring Instrument (TROPOMI) onboard the Sentinel-5 Precursor (S5P) satellite was launched on 13 October 2017 to provide the atmospheric composition for atmosphere and climate research. The S5P is a Sun-synchronous polar-orbiting satellite providing global daily coverage. The TROPOMI swath is 2600 km wide, and the ground resolution for most data products is 7.2×3.5 km2 (5.6×3.5 km2 since 6 August 2019) at nadir. The Finnish Meteorological Institute (FMI) is responsible for the development of the TROPOMI UV algorithm and the processing of the TROPOMI surface ultraviolet (UV) radiation product which includes 36 UV parameters in total. Ground-based data from 25 sites located in arctic, subarctic, temperate, equatorial and Antarctic areas were used for validation of the TROPOMI overpass irradiance at 305, 310, 324 and 380 nm, overpass erythemally weighted dose rate/UV index, and erythemally weighted daily dose for the period from 1 January 2018 to 31 August 2019. The validation results showed that for most sites 60 %–80 % of TROPOMI data was within ±20 % of ground-based data for snow-free surface conditions. The median relative differences to ground-based measurements of TROPOMI snow-free surface daily doses were within ±10 % and ±5 % at two-thirds and at half of the sites, respectively. At several sites more than 90 % of cloud-free TROPOMI data was within ±20 % of ground-based measurements. Generally median relative differences between TROPOMI data and ground-based measurements were a little biased towards negative values (i.e. satellite data < ground-based measurement), but at high latitudes where non-homogeneous topography and albedo or snow conditions occurred, the negative bias was exceptionally high: from −30 % to −65 %. Positive biases of 10 %–15 % were also found for mountainous sites due to challenging topography. The TROPOMI surface UV radiation product includes quality flags to detect increased uncertainties in the data due to heterogeneous surface albedo and rough terrain, which can be used to filter the data retrieved under challenging conditions.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi; ultrafiolett stråling